PENINGKATAN KEKOMPAKAN PEMUDA DENGAN MEREFORMASI KEPENGURUSAN ORGANISASI KEPEMUDAAN: Increasing Youth Cooperity by Reforming Management of Youth Organizations - Aminullah, Aminullah; Ramli, Ramli; Dewi, Ni Made Nia Bunga Surya; Astuti, Ni Kadek Puji (Yayasan Al-Amin Qalbu, 2023)
The goal in this service is to increase youth cohesiveness by reforming the management of youth organizations. The youth organization is the Change Pioneers Association (P4) of Bagik Manis Village, Sambelia sub-district, East Lombok Regency, NTB. Methods of implementation include preparation, implementation of management reforms and mentoring. The results of the dedication to organizational management reform were carried out through preparation for 2 months, namely February 2023 to April 2023, then the formation or election of new management was carried out on April 20 2023 through deliberations and voting. The mentoring process in the near future from April 2023 to July 2023 has resulted in the formation of a complete organizational structure, preparation of work programs, ratification of the organization by the Village, visits to the DPRD and meetings to discuss community issues